MODEL OF LEADING FOOD CROP COMMODITIES DEVELOPMENT IN WEST ACEH DISTRICT - Agustiar, Agustiar; Bagio, Bagio; Aulia, Muhammad Reza (Fakultas Pertanian, Universitas Janabadra, 2023)
Economic development the agriculture sector, especially superior food crops have a unique strategy in maintaining food crop production. Prime food crop in this area focused on agriculture development in supporting community livelihood. This research was conducted in the West Aceh district using a survey method, and this studies was prioritized on a food crop commodity basis involving farmers, agricultural extension workers and agents. The research was conducted in West Aceh district with survey methods. Studies related to oil as a commodity base involving farmers, extension agents and agency staff. Model analysis of the hierarchy, LQ, investment criteria, specialization and diversification. Study found that the development of prime commodities in West Aceh district has not been consistent with the potential of production centers in each sub-district. Several factors contributed to this inconsistency, among others. Elected as a prime commodity in West Aceh regency are paddy, zeamays, peanuts, cassava, soybean and sweet potato has been a prime of the community as a source of livelihood of the prime commodities sector. The best a strategy of commodity development in West Aceh is diversification strategy on the basis of the potential combinations, the type of commodity and infrastructure to support agribusiness. Each district as well as developed some commodity to anticipate the price fluctuations of commodity. Key Word: agriculture subsector, prime commodities, commodity agibusiness